Patterns of Forensic Practice - Harold Merskey (Pain Research and Management)
Forensic pain medicine has provided an interesting survey of medico-legal practice patterns among pain specialists (1). Members of the New England Pain Association responded to a 20-item questionnaire addressing specific areas of practice including the completion of disability forms, letters, reports to lawyers, depositions, testimony in court, record reviews and return-to-work forms. Respondents were asked to distinguish the medico-legal activities for their patients from those that occurred for third parties. The participants who responded included pain specialists from a range of disciplines represented by the membership of this regional pain society. The response rate was 67% with a total of 144 surveys returned.